Tardigrados en musgos de la Reserva El Diviso (Santander, Colombia) - Jerez J, J.H.=700 1 Narvaez P, E.X.; Restrepo M, R.
(Es, En)
Ilus., 19 ref.
Keywords: INVERTEBRADOS; TAXONOMIA; HABITAT; COLOMBIA; TARDIGRADOS; MICROHABITAT